A new modified technique of laparoscopic needle catheter jejunostomy: a 2-year follow-up study - Ye P; Zeng LP; Sun FH; An Z; Li ZB; Hu J (Dove Medical Press, 2016)
Peng Ye, Liping Zeng, Fenghao Sun, Zhou An, Zhoubin Li, Jian Hu Department of Thoracic Surgery, First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou, People’s Republic of China Background: The aim of this study was to establish a modified technique for performing laparoscopic needle catheter jejunostomy. Methods: From May 2011 to October 2013, laparoscopic needle catheter jejunostomy was performed in 21 patients with esophageal cancer. During the procedure, jejunal inflation was performed via a percutaneous 20-gauge intravenous catheter to facilitate the subsequent puncture of the jejunal wall by the catheter needle. The success rate, procedure time, complications, and short-term outcomes were evaluated. Results: All laparoscopic needle catheter jejunostomies were technically successful, with no perioperative mortality or conversion to a laparotomy. The operation required a mean time of 51.4±14.2 (range 27–80) minutes, and operative bleeding range was 5–20 mL. There was one reoperation required for one patient on postoperative day 5, because the feeding tube was accidentally pulled out during sleep, by patient himself, and the second laparoscopic jejunostomy for this patient was performed successfully. One patient had puncture site pain and was successfully treated with oral analgesics. Other complications, such as gastrointestinal bleeding, intestinal perforation, intestinal obstruction, tube dysfunction, pericatheter leakage, and infection at the skin insertion site, were not observed. The 30-day mortality rate was 4.8% (one out of 21), which was not attributed to the procedure. Enteral nutrition was gradually administered 24–48 hours after operation. Conclusion: The novel modified technique of laparoscopic needle catheter jejunostomy is a technically feasible, with a high technical success rate and low complication rate. Its specific advantage is simplicity and safety, and this modified approach can be considered for routine clinical use after long-term outcome evaluation. Keywords: esophageal cancer, laparoscopy, needle catheter jejunostomy